Efficient Vacuum‐Processed Light‐Emitting Diodes Based on Carbene–Metal–Amides. Issue 35 (9th July 2018) - Conaghan, Patrick J.; Menke, S. Matthew; Romanov, Alexander S.; Jones, Saul T. E.; Pearson, Andrew J.; Evans, Emrys W.; Bochmann, Manfred; Greenham, Neil C.; Credgington, Dan
Abstract: Efficient vacuum‐processed organic light‐emitting diodes are fabricated using a carbene–metal–amide material, CMA1. An electroluminescence (EL) external quantum efficiency of 23% is achieved in a host‐free emissive layer comprising pure CMA1. Furthermore external quantum efficiencies of up to 26.9% are achieved in host–guest emissive layers. EL spectra are found to depend on both the emissive‐layer doping concentration and the choice of host material, enabling tuning of emission color from mid‐green (Commission Internationale de l'Éclairage co‐ordinates [0.24, 0.46]) to sky blue ([0.22 0.35]) without changing dopant. This tuning is achieved without compromising luminescence efficiency (>80%) while maintaining a short radiative lifetime of triplets (<1 μs). Abstract : Vacuum‐processing can be used to fabricate reproducible high‐efficiency organic light‐emitting diodes (OLEDs) from carbene–metal–amides. The ability to tune the electroluminescence color through control of the emissive layer concentration and host material is demonstrated. External quantum efficiency is shown to only weakly depend on concentration, and host‐free OLEDs with maximum external quantum efficiency of 23% are reported in comparison to 26.9% in a host matrix.